Multi-omic detection of Mycobacterium leprae in archaeological human dental calculus. (23rd November 2020) - Fotakis, Anna K.; Denham, Sean D.; Mackie, Meaghan; Orbegozo, Miren Iraeta; Mylopotamitaki, Dorothea; Gopalakrishnan, Shyam; Sicheritz-Pontén, Thomas; Olsen, Jesper V.; Cappellini, Enrico; Zhang, Guojie; Christophersen, Axel; Gilbert, M. Thomas P.; et al.
Abstract : Mineralized dental plaque (calculus) has proven to be an excellent source of ancient biomolecules. Here we present a Mycobacterium leprae genome (6.6-fold), the causative agent of leprosy, recovered via shotgun sequencing of sixteenth-century human dental calculus from an individual from Trondheim, Norway. When phylogenetically placed, this genome falls in branch 3I among the diversity of other contemporary ancient strains from Northern Europe. Moreover, ancient mycobacterial peptides were retrieved via mass spectrometry-based proteomics, further validating the presence of the pathogen. Mycobacterium leprae can readily be detected in the oral cavity and associated mucosal membranes, which likely contributed to it being incorporated into this individual's dental calculus. This individual showed some possible, but not definitive, evidence of skeletal lesions associated with early-stage leprosy. This study is the first known example of successful multi-omics retrieval of M. leprae from archaeological dental calculus. Furthermore, we offer new insights into dental calculus as an alternative sample source to bones or teeth for detecting and molecularly characterizing M. leprae in individuals from the archaeological record. This article is part of the theme issue 'Insights into health and disease from ancient biomolecules'.